Experimental investigation on a novel integrated solar chimney and liquid desiccant system for simultaneous power and fresh water generation - Mahal, Sabah K.; Alimin, Ahmad J. (Asian Institute of Technology, 2020)
Electric power and water play a pivotal role in all aspects of daily life. In attempts to provide renewable energy-sourced systems for the concurrent generation of power and fresh water, a few studies have been conducted over the last two decades to combine solar chimney power plant (SCPP) with fresh water production systems (FWPS). These studies have mostly been theoretical approaches with significant feasibility limitations. In this article, a novel solar-powered hybrid generator of power and fresh water is presented, where SCPP has been combined with liquid desiccant system( LDS) to simultaneously produce power and fresh water. This combination utilizes the advantages of LDS of calcium chloride to turn the SCPP working air humidity into fresh water. A pilot plant of this technology was designed, constructed, and tested on an hourly basis over ten randomly selected days in October-December 2018. Consequently, its concept of operation was proven. It was concluded that using this technology and under daily averages of solar irradiance of 500 W/m2 and atmospheric air humidity ratio of 0.019 (kg water vapour/ kg dry air), a combination of power generation capacity higher than 50 MW could economically produce power and fresh water. Furthermore, an average of 5.6 l/hr of fresh water could be produced per 1 kg/s of SCPP working air. Nevertheless, the current technology enables using a wide controllable range (0%-100%) of SCPP produced power to generate fresh water.